Popular protest in China - O'Brien, Kevin J., 1957- (Harvard contemporary China series, 2008)
Do our ideas about social movements travel successfully beyond the democratic West? Unrest in China, from the dramatic events of 1989 to more recent stirrings, offers a rare opportunity to explore this question and to consider how popular contention unfolds in places where speech and assembly are tightly controlled.